Drgania Swobodne Belki przy Słabo Nieliniowych Warunkach Brzegowych - Piszczek, K.; Sobejko, L. (Engineering Transactions, 1965)
This paper gives a method for computing the natural frequency of a beam with one nonlinear boundary condition. The present paper brings a description of a computation method of the natural frequency in the more general case, in which two of the four boundary conditions (of elastic clamping at both ends) contain nonlinear terms. It is found that the same method may be applied in the case of more nonlinear conditions.